2002
DOI: 10.1097/00005392-200210020-00005
|View full text |Cite
|
Sign up to set email alerts
|

The Single Testis: Paternity After Presentation as Unilateral Cryptorchidism

Abstract: This study failed to indicate that paternity is diminished among men with a single testis compared with the general population, regardless of the origin of the loss. About 12% of unilateral impalpable testes judged to be impalpable on examination before surgery were found to be absent after surgical exploration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 12 publications
1
11
0
2
Order By: Relevance
“…Lee and co-authors, who performed a retrospective review of medical records and sent a detailed questionnaire to patients, concluded that unilateral cryptorchid men have a normal paternity rate [Lee et al, 1996]. It should be noted that in this study the authors did not rely upon the results of testicular biopsies.…”
Section: Paternity As a Fertility Indicator?mentioning
confidence: 94%
“…Lee and co-authors, who performed a retrospective review of medical records and sent a detailed questionnaire to patients, concluded that unilateral cryptorchid men have a normal paternity rate [Lee et al, 1996]. It should be noted that in this study the authors did not rely upon the results of testicular biopsies.…”
Section: Paternity As a Fertility Indicator?mentioning
confidence: 94%
“…Kombi nationstherapie einen höheren Wirkungs grad als die isolierte Gabe von LHRH Analoga oder HCG. Bis heute gibt es aber keine randomisierten Studien, die die Überlegenheit des einen oder anderen Vorgehens darlegen [24].…”
Section: Leitliniengerechte Therapieunclassified
“…Eine Möglichkeit, den Hoden in Bezug auf Fertilität zu beurteilen, ist der "Tubu lar Fertility Index" (TFI [24]. Des Weiteren offen barte sich auch kein zeitlich signifikanter Unterschied bis zur Konzeption -auch ein wichtiger Parameter zur Beurteilung der Fertilität.…”
Section: Introductionunclassified
“…8 Furthermore, another study failed to show a difference in paternity among men with monorchidism owing to an absent or removed testis, men with unilateral cryptorchidism treated with orchiopexy in childhood and controls. 9 In those patients with decreased fertility from bilateral disease, successful pregnancy is possible using testicular sperm extraction and intracytoplasmic sperm injection. 10 …”
Section: Cryptorchidismmentioning
confidence: 99%